Metallic material and joint comprising said metallic material and substrate
Patent Information
- Application Number
- JP2020206723
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-12-14
Smart Images

Figure 0007640258000001 
Figure 0007640258000002 
Figure 0007640258000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal material and a joined body including the metal material and a substrate. [Background technology]
[0002] In recent years, materials in which metal-based layers (hereinafter simply referred to as "metal layers") are laminated with an intermediate layer between them have been widely used in the semiconductor field. For example, the following Patent Document 1 discloses an electrostatic chuck on which a wafer or the like is placed and fixed in place during the manufacturing process of a semiconductor device, and describes that the electrostatic chuck comprises a material in which a tungsten layer and a silver solder are laminated with a nickel-plated layer between them. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-103393 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, according to the investigations of the present inventors, it was found that when metal layers are laminated with a nickel plating layer interposed therebetween, the adhesion between the metal layers is low due to the hard and brittle nature of the nickel plating layer. The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a metal material in which metal layers are laminated with high adhesion via an intermediate layer, and to provide a joined body including such a metal material and a substrate. [Means for solving the problem]
[0005] In order to achieve this object, the present invention provides a metal material having a laminated structure including a metal layer containing nickel, an oxide layer mainly composed of NiO formed on the metal layer, and a precious metal microparticle sintered body layer composed of precious metal microparticles formed on the oxide layer.
[0006] The inventors have discovered that a metal material can be obtained in which the metal layer and the sintered precious metal particle layer are laminated with high adhesion via an oxide layer mainly made of NiO by applying a paste-like (including slurry and ink-like; the same applies below) composition containing nickel fine particles onto a substrate mainly made of tungsten, drying the composition, and firing the composition at 1000°C in a reducing atmosphere to obtain a metal layer containing nickel, and then applying a paste containing precious metal fine particles onto the metal layer, drying the composition, and firing the composition, thereby completing the present invention.
[0007] In one preferred embodiment of the metallic material disclosed herein, the metallic layer comprises a nickel-tungsten alloy. Conventionally, the formation of a nickel-tungsten alloy (i.e., an intermetallic compound composed of nickel and tungsten) has been considered undesirable because it makes that part brittle. However, the technology disclosed herein makes it possible to provide a metal material in which a metal layer containing a nickel-tungsten alloy is laminated with high adhesion to a precious metal microparticle sintered body layer via an oxide layer mainly composed of NiO.
[0008] In a preferred embodiment of the metallic material disclosed herein, the nickel-tungsten alloy includes Ni4W. For the reasons described above, nickel-tungsten alloys including Ni4W are suitable targets for application of the technology disclosed herein.
[0009] In a preferred embodiment of the metallic material disclosed herein, the main constituent metallic element of the noble metal fine particles constituting the noble metal fine particle sintered layer is gold (Au). Gold (Au) has excellent thermal conductivity, electrical conductivity, etc., and therefore metal materials having a gold fine particle sintered layer are useful because they can be used in a variety of industrial products.
[0010] In one aspect for achieving the above object, there is provided a joined body comprising the metal material disclosed herein and a substrate. Such a bonded article is useful since it can be used in various industrial products.
[0011] In a preferred embodiment of the joint disclosed herein, the substrate is mainly composed of tungsten. A bonded body having such a structure can be suitably used in semiconductor products and the like.
[0012] In the joined body of this embodiment, a diffusion layer in which nickel is diffused into a tungsten matrix is preferably present between the substrate and the metal material, and the diffusion layer includes a portion in which the amount of nickel contained in the diffusion layer is at least 2 atomic % when the total number of tungsten and nickel atoms in the diffusion layer is taken as 100 atomic %.
[0013] The inventors discovered that when a metal layer containing nickel is obtained by applying a paste containing nickel fine particles onto a substrate mainly composed of tungsten, drying the paste, and then firing the paste at 1000°C in a reducing atmosphere, a diffusion layer in which nickel is diffused into a tungsten matrix exists between the substrate and the metal layer, and that the diffusion layer contains a portion containing at least 2 atomic % of nickel. Note that an embodiment in which nickel is diffused in a tungsten matrix at 2 atomic % or more has not been reported so far, and this is the first time that such an embodiment has been realized.
[0014] In the bonded body of this embodiment, preferably, there is a portion in which the amount of nickel contained in the diffusion layer is at least 2 atomic %, when the total number of tungsten and nickel atoms in the diffusion layer is taken as 100 atomic %, and the portion has a thickness of 5 nm or more. According to this configuration, a bonded body can be obtained in which a metal layer is formed on a base material with higher adhesion. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram showing a configuration of a metal material according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram illustrating a configuration of a bonded body according to an embodiment. [Diagram 3] 1 is a HAADF-STEM observation image (10,000x) showing the FIB treatment of the metal material according to Example 1. [Figure 4] 1 is a HAADF-STEM observation image (30,000x) showing the result of TEM-EDX element mapping of a thin section obtained after FIB processing of the metal material according to Example 1. [Diagram 5] 1 is a graph showing an HAADF-STEM observation image (500,000 times magnification) of a thin section obtained after FIB processing of the metal material of Example 1, and the results of TEM-EDX line analysis of a line portion P in the observation image. [Figure 6] 6 is a table showing the raw data constituting the S portion of the graph in FIG. 5. [Figure 7] 1 shows an HAADF-STEM observation image (30,000x) of a thin piece obtained after FIB processing of the metal material of Example 1, and electron diffraction patterns in areas A and B in the observation image. [Figure 8] 1 is an FE-SEM observation image (20,000 times) of a metal material included in a joint body according to Example 1. [Figure 9] 1 is an FE-SEM observation image (100,000 times) of a metal material included in a joint body according to Example 1. [Figure 10] 1 is a HAADF-STEM observation image (10,000x) showing the state of FIB processing on a metal material according to Comparative Example 1. [Figure 11] 1 is a HAADF-STEM observation image (30,000x) showing the results of TEM-EDX element mapping of a thin section obtained after FIB processing of a metal material according to Comparative Example 1. [Figure 12]1 is a graph showing an HAADF-STEM observation image (500,000 times magnification) of a thin section obtained after FIB processing of a metal material in Comparative Example 1, and the results of a TEM-EDX line analysis of a line portion Q in the observation image. [Figure 13] 13 is a table showing the raw data constituting part T of the graph in FIG. 12. [Figure 14] 1 shows an HAADF-STEM observation image (30,000x) of a thin piece obtained after FIB processing of a metal material according to Comparative Example 1, and electron diffraction patterns in areas A and B in the observation image. [Figure 15] 13 is a HAADF-STEM observation image (10,000x) showing the aspect of FIB processing on a metal material according to Comparative Example 2. [Figure 16] 1 is a HAADF-STEM observation image (30,000x) showing the results of TEM-EDX element mapping of a thin section obtained after FIB processing of a metal material according to Comparative Example 2. [Figure 17] 1 is a graph showing an HAADF-STEM observation image (500,000 times magnification) of a thin section obtained after FIB processing of a metal material according to Comparative Example 2, and the results of a TEM-EDX line analysis of a line portion R in the observation image. [Figure 18] 18 is a table showing the raw data constituting the U portion of the graph in FIG. 17. [Figure 19] 1 shows an HAADF-STEM observation image (30,000x) of a thin piece obtained after FIB processing of a metal material according to Comparative Example 2, and electron diffraction patterns in areas A and B in the observation image. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Preferred embodiments of the present invention will be described below. Matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. The following embodiments are not intended to limit the technology disclosed herein. In addition, in the drawings shown in this specification, the same reference numerals are used to describe members and parts that perform the same function. The dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In this specification and claims, when a certain numerical range is described as A to B (A and B are arbitrary numerical values), it means A or more and B or less. Therefore, the case where it is more than A and less than B is also included.
[0017] <Metal material composition> Fig. 1 is a schematic diagram showing the configuration of a metallic material 1 according to one embodiment. As shown in Fig. 1, the metallic material 1 roughly comprises a metal layer 4, an oxide layer 3 formed on the metal layer, and a precious metal fine particle sintered body layer 2 formed on the oxide layer. Each component will be described below.
[0018] <Metal layer> The metal layer 4 is a layer containing nickel. The metal layer 4 may also contain a nickel-tungsten alloy. Examples of such nickel-tungsten alloys include NiW, Ni2W, and Ni4W. Here, as one embodiment of the metal layer 4, in addition to the nickel-tungsten alloy layer as described above, a nickel layer may be further included. The configuration of the metal layer 4 can be changed, for example, depending on the content of nickel fine particles in the nickel fine particle paste described in <Metal material and method for producing joint body>. When the content of nickel fine particles in the nickel fine particle paste is, for example, 70% by weight to 90% by weight when the nickel fine particle paste is taken as 100% by weight, the configuration as described above can be obtained.
[0019] <Oxide layer> The oxide layer 3 is a layer mainly made of NiO (nickel (II) oxide). Here, "a layer mainly made of NiO" means that the component that is most abundant by weight among the components that constitute the layer is NiO. The oxide layer 3 may be a layer that preferably contains 90% by weight or more, 95% by weight or more, or 99% by weight or more of NiO. Examples of components other than NiO include various metal elements and nonmetal elements. The thickness of the oxide layer 3 is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but it may be preferably 10 nm or more, 20 nm or more, and more preferably 30 nm or more in the lamination direction of the metal material 1. With this configuration, it is possible to obtain a metal material 1 in which the metal layer 4 and the precious metal fine particle sintered body layer 2 are formed with higher adhesion. Typically, the thickness of the oxide layer 3 may be an embodiment in which a portion of 100 nm or less (for example, about 50 nm) is present. The "thickness of the oxide layer" (also referred to as the thickness of the NiO layer) refers to the value obtained when the shortest distance from the surface of the metal layer 4 to the surface of the oxide layer 3 is measured in SEM microscope observation.
[0020] <Sintered precious metal particle layer> The precious metal microparticle sintered body layer 2 is a sintered body layer made of precious metal microparticles. In this specification and claims, "precious metal microparticles" refer to precious metal microparticles whose main constituent metal element is a precious metal element, and the type of precious metal is not limited. Typical examples include gold (Au), silver (Ag), palladium (Pd), platinum (Pt), rhodium (Rh), etc., or alloys thereof. In addition, since gold (Au) has excellent thermal conductivity, electrical conductivity, etc., a metal material having a gold microparticle sintered body layer is useful because it can be used in various industrial products. Here, the main constituent metal element means a metal element that is the main constituent of the precious metal microparticles. Note that the precious metal microparticles are ideally composed only of precious metal elements, but may contain various metal elements and nonmetal elements as impurities. For example, 90% by weight or more, 95% by weight or more, or 98% by weight or more of the total may be composed of the main constituent metal elements. Note that the organic matter content of the total weight (100% by weight) of the precious metal microparticles (referring to the aggregate before calcination) measured based on TG-DTA is preferably approximately 2% by weight or less, further preferably 1.5% by weight or less, and particularly preferably 1% by weight or less.
[0021] <Construction of the joint> Fig. 2 is a schematic diagram showing a configuration of a bonded body 10 according to one embodiment. Note that Fig. 2 shows a case where the base material is mainly composed of tungsten, but it is not intended that the present invention be limited to such a configuration. 2, the bonded body 10 roughly comprises a metal material including a metal layer 14, an oxide layer 13 formed on the metal layer, and a precious metal fine particle sintered layer 12 formed on the oxide layer, and a tungsten base material 16. In this embodiment, a diffusion layer 15 exists between the metal material and the tungsten base material 16. Each component will be described below. Note that the metal layer 14, the oxide layer 13, and the precious metal fine particle sintered layer 12 have the same configuration as the metal layer 4, the oxide layer 3, and the precious metal fine particle sintered layer 2, respectively, and therefore detailed description thereof will be omitted.
[0022] <Base material> The tungsten base material 16 is a base material mainly composed of tungsten. The bonded body 10 having a base material of this composition can be suitably used for semiconductor products and the like. The term "base material mainly composed of tungsten" means that the component that is contained most abundantly by weight among the components that constitute the base material is tungsten. The tungsten base material 16 may be a base material that preferably contains 90% by weight or more, 95% by weight or more, or 99% by weight or more of tungsten. In addition, components other than tungsten include various metal elements and nonmetal elements as unavoidable impurities. The type of the substrate provided in the bonded body disclosed herein is not limited to tungsten, and is not particularly limited as long as the effect of the technology disclosed herein is exhibited. For example, other than tungsten, those mainly composed of tungsten carbide, ceramics, various metal materials, etc. can be preferably used. In addition, as a method for producing the bonded body disclosed herein using the above-mentioned substrate, for example, a method of mixing tungsten nanoparticles in a nickel fine particle paste composition at a ratio of Ni:W=4:1 to 5:1 (molar ratio), applying the paste on the substrate, and firing the paste under a reducing atmosphere or the like can be mentioned.
[0023] <Diffusion layer> In the joined body 10 according to this embodiment, a diffusion layer 15 exists between the tungsten base material 16 and the metal layer 14. The diffusion layer 15 is a layer in which nickel is diffused into a tungsten matrix. The diffusion layer 15 can also be referred to as a layer in which nickel is dissolved in tungsten. In diffusion layer 15, there is a portion where the amount of nickel contained in the diffusion layer is at least 2 atomic % when the total number of tungsten and nickel atoms in the diffusion layer is taken as 100 atomic %. In diffusion layer 15, there may be a portion where the amount of nickel contained in the diffusion layer is 3 atomic % or more, 4 atomic % or more, or 5 atomic % or more. Typically, the amount of nickel contained in diffusion layer 15 may be 10 atomic % or less. The thickness of the diffusion layer 15 is not particularly limited as long as the effect of the technology disclosed herein is exhibited. In the diffusion layer 15, when the total number of tungsten and nickel atoms in the diffusion layer is taken as 100 atomic %, the thickness of the part where the amount of nickel contained in the diffusion layer is at least 2 atomic % is preferably 5 nm or more, more preferably 10 nm or more, 20 nm or more, 30 nm or more, 40 nm or more, and even more preferably 50 nm or more. For example, there may be a part of 60 nm or more, 80 nm or more, or 100 nm or more. With this configuration, a bonded body 10 in which the metal layer 14 is formed on the tungsten base material 16 with higher adhesion can be obtained. Typically, the thickness of the diffusion layer 15 may be 200 nm or less.
[0024] <Metal materials and methods for producing joints> Next, an example of a method for producing the metal material 1 and the bonded body 10 will be described. First, a nickel microparticle paste containing nickel microparticles is applied onto a substrate mainly composed of tungsten, dried, and then fired at 1000°C in a reducing atmosphere to obtain a metal layer 14 containing nickel. Next, a precious metal microparticle paste containing precious metal microparticles is applied onto the metal layer 14, dried, and then fired. This makes it possible to obtain a metal material 1 in which the metal layer 14 and the precious metal microparticle sintered layer 12 are laminated with high adhesion via an oxide layer 13 mainly composed of NiO (and a bonded body 10 in which the metal material and the tungsten substrate 16 are laminated via a diffusion layer 15).
[0025] Here, the size of the nickel fine particles contained in the nickel fine particle paste and the precious metal fine particles contained in the precious metal fine particle paste is, for example, preferably 300 nm or less in average particle diameter, more preferably 200 nm or less, and can be, for example, 30 nm to 200 nm. In this specification and claims, "average particle diameter" means a cumulative 50% particle diameter in a particle size distribution based on the number measured based on electron microscope observation. Specifically, the particle size distribution can be created based on the circle equivalent diameter obtained for 100 or more particles (for example, 100 to 1000 particles) by observing particles (here, nickel fine particles, precious metal fine particles) at an appropriate magnification (for example, 50,000 times) using, for example, a scanning electron microscope (SEM). The content of the fine particles (here, nickel fine particles, precious metal fine particles) in the paste is not particularly limited, but when the entire paste is taken as 100% by weight, it can be generally 30% by weight or more, typically 40 to 95% by weight, for example, within the range of 50 to 70% by weight. Then, by kneading the nickel fine particles or noble metal fine particles as described above, a solvent, and, if necessary, a binder or other components, a paste-like composition (i.e., nickel fine particle paste, noble metal fine particle paste) can be prepared. Here, as the binder, for example, acrylic resin, cellulose-based resin, or other resins can be used alone or in combination of two or more. The content of the binder contained in the paste is not particularly limited, but when the entire paste is taken as 100% by weight, it can be approximately 30% by weight or less, typically 0.1 to 25% by weight, for example, in the range of 10 to 20% by weight. In addition, as the solvent, for example, petroleum-based hydrocarbons (particularly aliphatic hydrocarbons) such as mineral spirits, ethylene glycol and diethylene glycol derivatives, toluene, xylene, butyl carbitol (BC), terpineol, menthanol, menthol, isobornyl acetate, phenylpropylene glycol, and other solvents can be used alone or in combination of two or more. The content of the solvent in the paste is not particularly limited, but when the entire paste is taken as 100% by weight, it can be generally 70% by weight or less, typically 5 to 60% by weight, for example, in the range of 10 to 40% by weight.
[0026] <Applications of metal materials and joints> The metal material 1 and the joined body 10 can be suitably used for various industrial products, etc. The metal material 1 can also be used in an embodiment in which, for example, another layer (e.g., a metal layer) is joined to the precious metal sintered body layer 2 and / or the metal layer 4. The joined body 10 can also be used in an embodiment in which, for example, another layer (e.g., a metal layer) is joined to the precious metal fine-particle sintered body layer 12 and / or the base material 16.
[0027] Examples using the metal materials (and joints) disclosed herein will be described below, but these examples are not intended to limit the present invention.
[0028] 1. Preparation of Gold Microparticle Paste 50 mL of octanol (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 20.6 g of chloroauric acid tetrahydrate (Insuisho Precious Metals Chemical Co., Ltd.), and the resulting solution was cooled and stirred in an ice bath. Next, n-octylamine (a product of Fujifilm Wako Pure Chemical Industries, Ltd.) was added little by little to the above solution while suppressing heat generation, to prepare a chloroauric acid-octylamine complex formation solution, in an amount equivalent to 10 molar equivalents of the gold content. This complex-forming solution was subjected to a reduction treatment in which it was heated in an oil bath at 140°C in an air atmosphere for 3 hours while being stirred, thereby reducing the gold ions and synthesizing gold nanoparticles. After that, the reaction solution was naturally cooled, industrial alcohol (a product of Amano Chemical Industry) was added, the gold particles were precipitated, and the supernatant was removed by decantation. After repeating this operation three times, industrial alcohol was added and centrifuged at 3000 rpm for 3 minutes three or more times to remove the supernatant. The gold particles obtained here were dried at room temperature, and their average particle diameter was measured and found to be 40 nm. Then, menthanol was added as a dispersion medium, and the mixture was left to stand for 3 hours or more, and then centrifuged to perform solvent replacement. The concentration of the obtained wet powder was adjusted to 70 to 80% by weight, and the mixture was mixed and dispersed in a rotating mixer. This resulted in a gold particle paste.
[0029] 2. Preparation of Zygotes Example 1: Nickel microparticles (average particle size: 180 nm), acrylic resin, and isobornyl acetate were mixed to prepare a nickel microparticle paste. The content of each component was 50% by weight of nickel microparticles, 10% by weight of acrylic resin, and the remainder was solvent, assuming the nickel microparticle paste to be 100% by weight. Next, the nickel fine particle paste prepared as described above was applied onto a tungsten substrate (length x width x thickness: 15 mm x 15 mm x 0.3 mm, the tungsten substrate used below was of a similar size) so that the nickel film thickness after firing would be about 1 to 2 μm. Then, after drying at 120°C for 10 minutes, it was fired at 1000°C for 30 minutes in an atmosphere of 3% hydrogen-nitrogen gas (i.e., in a reducing atmosphere), to form a nickel fired film (corresponding to a metal layer containing nickel, the same applies below). Next, the gold fine particle paste prepared as described above was applied onto the obtained nickel fired film so that the film thickness after firing would be about 2 μm. Then, this was dried at 60° C. for 1 hour, and then heated at 10° C. / min and fired at 300° C. for 30 minutes to form a gold fine particle fired film (corresponding to a gold fine particle sintered body layer, the same applies below). This resulted in the bonded body according to Example 1.
[0030] Example 2: Silver oxalate was added to a mixture of isodecanol and n-butanol, and the mixture was heated in an oil bath at 100°C while stirring. After heating for 1 hour, the mixture was naturally cooled to room temperature. Then, the silver particles were precipitated by centrifuging at 6000 rpm for 5 minutes, and the supernatant was removed. The obtained silver particles were dried at room temperature, and the average particle diameter was measured and found to be 80 nm. Then, phenylpropylene glycol was added, the mixture was stirred with a spatula, and the silver particles were precipitated by centrifuging at 6000 rpm for 5 minutes again, and the supernatant was removed. This was repeated three times to obtain a silver particle paste. The content of each component was such that, when the above silver particle paste was 100% by weight, the silver particles were 80 to 90% by weight, and the remainder was the solvent. A bonded body according to Example 2 was produced in the same manner as in Example 1, except that the silver fine particle paste produced as described above was used instead of the gold fine particle paste.
[0031] Comparative Example 1: The same operation as in Example 1 was carried out, except that instead of applying nickel fine particle paste, an electric nickel plating film was formed on a tungsten substrate so that the film thickness after firing would be about 1 μm. As a result, the obtained gold fine particle fired film did not adhere to the electric nickel plating fired film, and became a separate film.
[0032] Comparative Example 2: The same operation as in Example 1 was carried out, except that an electroless nickel plating film was formed on a tungsten substrate so that the film thickness after firing would be about 1 μm, instead of applying a nickel fine particle paste. As a result, the obtained gold fine particle fired film was not adhered to the electroless nickel plating fired film, and was a single film.
[0033] Comparative Example 3: A tungsten substrate was coated with a water gold liquid (manufactured by Noritake Co., Ltd.) so that the film thickness after firing would be about 200 to 300 nm. This was then dried at 60°C for 1 hour, and then fired at 500°C for 30 minutes to form a water gold fired film. The gold fine particle paste was coated on the water gold fired film using a metal mask of 10 mm x 10 mm x 20 μm. This was then dried at 60°C for 1 hour, and then heated at a rate of 10°C / min and fired at 250°C for 30 minutes to form a gold fine particle fired film. As a result, the obtained gold fine particle fired film was not adhered to the water gold fired film, but was a separate film.
[0034] Comparative Example 4: Gold particles, polyimide resin, and γ-butyrolactone were mixed to prepare a gold particle-containing polyimide resin paste. Next, the gold particle-containing polyimide resin paste prepared as described above was applied onto a tungsten substrate. This was then dried at 130°C for 15 minutes and 180°C for 30 minutes, and then heated at 10°C / min and heat-treated at 280°C for 50 minutes to form a gold particle-containing polyimide resin layer. At this time, the solvent was almost completely removed. The gold particle paste was applied onto the gold particle-containing polyimide resin layer, dried at 60°C for 1 hour, heated at 10°C / min, and baked at 250°C for 30 minutes to form a gold particle baked film. As a result, the obtained gold particle baked film was not adhered to the gold particle-containing polyimide resin layer, and was a single film.
[0035] Comparative Example 5: Gold particles, a thermosetting epoxy resin, a curing agent, and Terpineol C were mixed together to prepare a gold particle-containing epoxy resin paste. Next, the gold particle-containing epoxy resin paste prepared as described above was applied onto a tungsten substrate. When this was dried at 60°C for 1 hour, the gold particle-containing epoxy resin paste lost its fluidity and was adhered to the tungsten substrate. The metal fine particle paste was applied onto the obtained gold particle-containing epoxy resin layer, dried at 60°C for 1 hour, and then heated at a rate of 10°C / min and heat-treated at 250°C for 30 minutes to harden the epoxy resin and form a gold fine particle baked film. As a result, the obtained gold fine particle baked film was not adhered to the gold particle-containing epoxy resin layer and was a single film.
[0036] Comparative Example 6: Except for not applying the nickel fine particle paste, the same operation as in Example 1 was carried out. As a result, the obtained gold fine particle fired film was not adhered to the tungsten substrate, and was a single film.
[0037] Comparative Example 7: The gold particle paste was applied to a glass substrate using a metal mask of 1 cm x 1 cm x 100 μm and squeezed with a rubber squeegee. After drying at 60°C for 1 hour, the temperature was increased at a rate of 10°C / min and baked at 300°C for 30 minutes. As a result, the obtained gold particle baked film was a separate film that did not adhere to the glass substrate.
[0038] Comparative Example 8: The gold particle paste was applied to a nickel substrate using a metal mask of 1 cm x 1 cm x 100 μm and squeezed with a rubber squeegee. After drying at 60°C for 1 hour, the temperature was raised at 10°C / min and sintered at 300°C for 30 minutes. As a result, the gold particle sintered film obtained did not adhere to the nickel substrate and was a separate film.
[0039] 3. Evaluation of adhesion of bonded bodies Adhesion evaluation was performed on the bonded bodies obtained in Examples 1 and 2. Specifically, in each bonded body, cellophane tape was attached to the tungsten substrate and the calcined film of precious metal fine particles, and when the tape was pulled up at 90°, it was confirmed whether the calcined film of precious metal fine particles peeled off. As a result, no peeling was observed in either Example 1 or 2.
[0040] 4. Cross-sectional observation of metal materials according to Example 1 and Comparative Examples 1 and 2 Cross-sectional observation was performed on the metal materials according to Example 1 and Comparative Examples 1 and 2. Here, the metal material according to Example 1 represents the metal material at the time when a fired nickel film was formed on the tungsten substrate. The metal material according to Comparative Example 1 represents the metal material at the time when an electric nickel plating fired film was formed on the tungsten substrate. And the metal material according to Comparative Example 2 represents the metal material at the time when an electroless nickel plating fired film was formed on the tungsten substrate. The test contents are described in detail below. In the following description, only the metal material according to Example 1 of Examples 1 and 2 is described, but it was confirmed that the metal material according to Example 2 (i.e., the one at the time when the nickel fired film was formed on the tungsten substrate) also had the same structure (composition) as Example 1. First, as shown in Figs. 3, 10, and 15, the metal material according to each example was filled with resin, and then FIB (Focused Ion Beam) processing was performed on the area surrounded by a frame line to thin the metal material. Then, EDX (Energy Dispersive X-ray) element mapping and line analysis were performed on the cross section of the thin piece. Here, Figs. 4, 11, and 16 are HAADF-STEM observation images (30,000 times magnification) showing the results of TEM-EDX element mapping on the thin piece obtained after FIB processing of the metal material according to Example 1, Comparative Example 1, and Comparative Example 2, respectively. Also, Figs. 5, 12, and 17 are graphs showing HAADF-STEM observation images (500,000 times magnification) of the thin piece obtained after FIB processing of the metal material according to Example 1, Comparative Example 1, and Comparative Example 2, respectively, and the results of line analysis on the TEM-EDX line parts (P, Q, and R, respectively) in the observation images. Figures 6, 13, and 18 are tables listing the raw data constituting the S, T, and U portions of the graphs in Figures 5, 12, and 17. The S, T, and U portions represent the portions in the graphs in Figures 5, 12, and 17 from when the increase in the atomic % of tungsten slows down to when tungsten reaches 100 atomic %. Furthermore, a selective area diffraction (SAD) pattern was obtained for the cross section of the thin section of each example. Figures 7, 14, and 19 show HAADF-STEM observation images (30,000 times magnification) of the thin sections obtained after FIB processing of the metal materials of Example 1, Comparative Example 1, and Comparative Example 2, respectively, and electron diffraction patterns in areas A and B in the observation images. Based on these data, the constitution (composition) of the metal material in each example was confirmed. EDX element mapping, line analysis, and acquisition of SAD patterns were performed using EM-002BF manufactured by Topcon Corporation.
[0041] For the thin piece of the metal material according to Example 1, the mapping of nickel and tungsten as shown in FIG. 4 was confirmed. In addition, as shown in the graph of the TEM-EDX line analysis in FIG. 5, a diffusion layer in which nickel is diffused into the tungsten matrix was confirmed between the nickel fired film and the tungsten substrate. Here, such a diffusion layer is defined as the portion from the point where the values of the atomic % of nickel and the atomic % of tungsten are reversed to the point where the atomic % of tungsten reaches 100 atomic % in the graph of FIG. 5 (see the solid line arrow portion in the graph of FIG. 5. The diffusion layers in the graphs of FIG. 12 and FIG. 17 are defined in the same way). It was also confirmed that the diffusion layer had a thickness of 40 nm in the direction in which the tungsten substrate and the nickel fired film were laminated. From FIG. 6, it was confirmed that in the portion of 44.0 nm to 74.2 nm thick, which corresponds to the S portion, the average atomic % of nickel was 4.4 atomic % (=61.7 / 14) (i.e., 2 atomic % or more). From this, it was found that in the region corresponding to the diffusion layer, there was a portion where the amount of nickel diffused was at least 2 atomic %, and the thickness of this portion was 5 nm or more. In addition, the TEM-EDX line analysis results confirmed the presence of an overlapping portion in a region of about 40 nm near the interface between tungsten and nickel, as determined from the HAADF-STEM observation image. Here, the overlapping portion refers to the portion in the graph of Figure 5 where the atomic percentages of nickel and tungsten change at a nearly constant rate (see the dashed arrow portion in the graph of Figure 5. The overlapping portions in the graphs of Figures 12 and 17 are defined in the same way). 7, it was confirmed that the A region of the above flake contains Ni, NiO, Ni4W, and W, and the B region contains W. From this, it was confirmed that the nickel fired film contains Ni4W, and furthermore, a NiO layer is formed on the nickel fired film. Here, Fig. 8 and Fig. 9 are images obtained when the cross section of the metal material included in the bonded body according to Example 1 was polished by ion milling and the interface was observed using a FE-SEM (apparatus used: S-8230, manufactured by Hitachi Technology Co., Ltd.). From Fig. 8 and Fig. 9, it was confirmed that a metal material having a layered structure including a Ni4W layer 23, a NiO layer 25 formed on the Ni4W layer, and a gold microparticle sintered body layer 22 made of gold microparticles formed on the NiO layer was formed on a tungsten substrate 24. It was also confirmed that the thickness of the NiO layer was about 50 nm.
[0042] Next, for the thin piece of the metal material according to Comparative Example 1, the mapping of nickel and tungsten as shown in FIG. 11 was confirmed. In addition, as shown in the graph of the TEM-EDX line analysis in FIG. 12, a diffusion layer in which nickel is diffused into the tungsten matrix was confirmed between the electrolytic nickel plating fired film and the tungsten substrate. It was confirmed that such a diffusion layer exists for 50 nm in the direction in which the tungsten substrate and the electrolytic nickel plating fired film are laminated (see the solid arrow portion in the graph in FIG. 12). In addition, from FIG. 13, it was confirmed that the average value of the atomic % of nickel was 4.6 atomic % (=68.3 / 15) in the portion of thickness 48.7 nm to 96.0 nm corresponding to the T portion. In addition, the results of the TEM-EDX line analysis confirmed the presence of an overlapping portion in a region of approximately 25 nm near the interface between tungsten and nickel as determined from the HAADF-STEM observation image (see the portion indicated by the dashed arrow in the graph in Figure 12). Furthermore, as shown in Fig. 14, it was confirmed that the A region of the above-mentioned thin piece contains Ni4W and W, and the B region contains W. In other words, it was confirmed that a NiO layer was not formed on the electrolytic nickel plating fired film.
[0043] Next, for the thin piece of the metal material according to Comparative Example 2, the mapping of nickel and tungsten as shown in FIG. 16 was confirmed. In addition, as shown in the graph of the TEM-EDX line analysis in FIG. 17, a diffusion layer in which nickel is diffused into the tungsten matrix was confirmed between the electroless nickel plating baked film and the tungsten substrate. It was confirmed that such a diffusion layer exists for 100 nm in the direction in which the tungsten substrate and the electroless nickel plating baked film are laminated (see the solid line arrow portion in the graph in FIG. 17). In addition, from FIG. 18, it was confirmed that the average value of the atomic % of nickel was 5.2 atomic % (=98.9 / 19) in the part with a thickness of 76.0 nm to 146.0 nm, which corresponds to the U portion. In addition, the results of the TEM-EDX line analysis confirmed the presence of an overlapping portion over a region of approximately 100 nm near the interface between tungsten and nickel as determined from the HAADF-STEM observation image (see the portion indicated by the dashed arrow in the graph in Figure 17). 19, it was confirmed that the A region of the above-mentioned thin piece contained Ni4W and W, and the B region contained W. That is, it was confirmed that the NiO layer was not formed on the electroless nickel plating fired film.
[0044] As is clear from the results of 3 and 4 above, in a metal material in which a nickel sintered film (corresponding to a metal layer containing nickel) and a precious metal microparticle sintered film (corresponding to a precious metal microparticle sintered layer) are laminated via an oxide layer mainly composed of NiO, it was confirmed that the nickel sintered film and the precious metal microparticle sintered film have high adhesion. The following is not particularly limited, but it can be considered that the formation of a NiO layer between the fired nickel film and the fired precious metal fine particle film results in a highly adhesive metal material (and a bonded body including the metal material and a substrate). Specifically, it can be considered that the presence of a NiO layer on the fired nickel film improves the affinity with the precious metal fine particle paste, and the fired nickel film and the fired precious metal fine particle film are bonded together. And, on the liquid gold film where the residue after firing is only gold as in Comparative Example 3, or on the substrate as in Comparative Examples 6 to 8, the affinity with the gold fine particle paste is not high, so only sintering of the gold fine particles in the paste progresses, and it is difficult to bond to the substrate or film, and therefore it can be considered that peeling occurs. It is believed that the NiO layer was formed by the reaction of oxygen attached to the nickel fine particles with the nickel fine particles during firing at 1000° C. In addition, it is believed that the NiO layer was not formed after firing because sufficient oxygen was not attached to the electric nickel plating film and the electroless nickel plating film to generate NiO. In this way, the technology disclosed herein can provide a metal material in which metal layers are laminated with high adhesion via an intermediate layer, and a bonded body including the metal material and a substrate. [Explanation of symbols]
[0045] 1 Metal materials 2,12 Precious metal fine particle sintered layer 3,13 Oxide layer 4,14 metal layer 10 zygote 15 Diffusion Layer 16,24 Tungsten substrate 22 Gold fine particle sintered layer 23 Ni4W layer 25 NiO layer P, Q, R line parts S, T, U Part showing the amount of nickel contained in the diffusion layer
Claims
1. A substrate containing 99% by weight or more of tungsten; A metal material formed on the substrate; and A joint comprising: Here, the metal material is A metal layer including nickel; an oxide layer mainly composed of NiO formed on the metal layer; a precious metal fine particle sintered layer formed on the oxide layer and made of precious metal fine particles; A bonded body having a laminated structure comprising:
2. The joint of claim 1, wherein the metal layer comprises a nickel-tungsten alloy.
3. The joint according to claim 2, wherein the nickel-tungsten alloy comprises Ni 4 W.
4. The joint body according to claim 1, wherein the main constituent metal element of the precious metal microparticles constituting the precious metal microparticle sintered layer is gold (Au).
5. a diffusion layer in which nickel is diffused into a tungsten matrix is present between the substrate and the metal material; The joint body according to any one of claims 1 to 4, characterized in that in the diffusion layer, there is a portion in which the amount of nickel contained in the diffusion layer is at least 2 atomic % when the total number of tungsten and nickel atoms in the diffusion layer is taken as 100 atomic %.
6. 6. The joined body according to claim 5, wherein the diffusion layer has a thickness of 5 nm or more, and the diffusion layer contains nickel at an amount of at least 2 atomic % when the total number of tungsten and nickel atoms in the diffusion layer is taken as 100 atomic %.
Citation Information
Patent Citations
Method of producing ceramic multilayer circuit board
JP1984171195A
Multilayer plating method
JP1989083686A
Metal coating film and its formation method
JP2006210197A
Metal particulate dispersion and method for forming metal film by using the same
JP2006321948A
Electrostatic chuck
JP2010103393A